2017
DOI: 10.3389/fnbeh.2017.00116
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Fear Extinction in the Basolateral Amygdala by Dopamine D2 Receptors Accompanied by Altered GluR1, GluR1-Ser845 and NR2B Levels

Abstract: The amygdala, a critical structure for both Pavlovian fear conditioning and fear extinction, receives sparse but comprehensive dopamine innervation and contains dopamine D1 and D2 receptors. Fear extinction, which involves learning to suppress the expression of a previously learned fear, appears to require the dopaminergic system. The specific roles of D2 receptors in mediating associative learning underlying fear extinction require further study. Intra-basolateral amygdala (BLA) infusions of a D2 receptor ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Plasticity in the amygdala and IL underlie acquisition and consolidation of fear extinction memories ( Duvarci and Pare, 2014 ; Maren et al, 2013 ; Pape and Pare, 2010 ; Sotres-Bayon and Quirk, 2010 ; Tovote et al, 2015 ). Furthermore, DA signaling in the amygdala and IL has been shown to play an important role in fear extinction ( Abraham et al, 2014 ; Haaker et al, 2013 ; Hikind and Maroun, 2008 ; Mueller et al, 2010 ; Shi et al, 2017 ; Whittle et al, 2016 ). Interestingly, optogenetic inhibition of DA neurons during US omission has been found to prevent extinction-related plasticity in the amygdala and IL ( Luo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Plasticity in the amygdala and IL underlie acquisition and consolidation of fear extinction memories ( Duvarci and Pare, 2014 ; Maren et al, 2013 ; Pape and Pare, 2010 ; Sotres-Bayon and Quirk, 2010 ; Tovote et al, 2015 ). Furthermore, DA signaling in the amygdala and IL has been shown to play an important role in fear extinction ( Abraham et al, 2014 ; Haaker et al, 2013 ; Hikind and Maroun, 2008 ; Mueller et al, 2010 ; Shi et al, 2017 ; Whittle et al, 2016 ). Interestingly, optogenetic inhibition of DA neurons during US omission has been found to prevent extinction-related plasticity in the amygdala and IL ( Luo et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian systems, separable populations of dopamine neurons project to the NAc, amygdala and mPFC 16 and distinct calcium changes have been reported in different VTA-dopamine terminal fields 17 , 18 . Importantly, dopamine receptor activation in the vmPFC, amygdala and NAc modulates extinction learning and memory 19 23 . This suggests that based on their projection targets, distinct subpopulations of dopamine neurons may differentially regulate fear extinction.…”
Section: Introductionmentioning
confidence: 99%
“…A growing literature indicates that dopamine plays an important role in fear extinction (Abraham et al, 2014). A previous study reported that activation of D2 receptors facilitates fear extinction and that blockade of D2 receptors impairs fear extinction (Shi et al, 2017). Furthermore, a blockade of the D1 receptor in the BLA before an extinction session disrupted fear extinction (Hikind and Maroun, 2008).…”
Section: Discussionmentioning
confidence: 99%